Unusual demonstration of paradental cyst affecting impacted lower third molar - Mustafa, Nazih Shaban; Ghazali, Ahmad Badruddin; Khalid, Rafiq (https://saspublishers.com, 2023)
The paradental cyst is an odontogenic cyst of inflammatory origin, localised on the buccal, distal, less common mesial aspects of partially erupted mandibular third molars, with the history of recurrent pericoronitis. This case report highlights paradental cyst that presented in the central of furcation area of a partially erupted mandibular third molar. Extra and intraoral examination, Dental Panoramic Tomograph (DPT) in addition to Cone Beam Computed Tomography (CBCT) have been done for the assessment and surgical planning accordingly. Tooth was removed surgically without any complications the tooth was removed in total with the cystic lesion attached between the two roots. The sample was sent for histopathological study which came out with the diagnosis of a paradental cyst. In conclusion this type of cysts is in unusual location, careful examination, radiographic assessment with histologic study is required in diagnosis of such lesion.